Restoration of Anterior Dental Erosion with a Combination of Veneers and Crowns: A 3-Year Case Report - Abreu, Amara; Rucker, M. Bryan; Loza, María A.; Brackett, William W. (Puerto Rico Health Sciences Journal, 2015)
This report describes the conservative management of a 40-year-old female patient with smooth, eroded facial enamel affecting her maxillary anterior and some posterior teeth. Using conventional enamel bonding, pressed leucite-reinforced laminate veneers were used to restore the length, contour, and esthetics of the maxillary right canine, as well as of the right lateral and both central incisors; at the same time, it was necessary to restore the maxillary left lateral incisor, canine, and first premolar of the same quadrant with all-ceramic crowns of the same material. The patient has been followed for 3 years and demonstrates a good esthetic outcome with no shade discrepancy between the two types of restoration. Apparently, the tooth structure, though eroded, was able to provide an adequate bonding substrate for these adhesive restorations.